The effect of high- intensity interval swimming training on irisin and metabolic syndrome in postmenopausal overweight women - akram jafari; elham shafaghat dehkordi (Sport Sciences and Health Research, 2021)
Background: Transmembrane protein ﬁbronectin type III domain-containing protein 5 (FNDC5) is as a myokine, metabolic regulator and potential therapeutic agent which is known as a potential trait for metabolism and obesity.Aim: The purpose of this study was to evaluate the effect of high intensity interval swimming training on circulating irisin and some metabolic syndrome in postmenopausal overweight women.Materials and Methods: Thirty postmenopausal overweight women (55.73 ± 2.66 years, 26.72±2.33 kg/m2) were randomized into high intensity interval swimming training (n=15; HIIT) and control groups (n=15; CON). HIIT performed 6–10×30 s swimming interspersed by 2 min recovery for an 8-week period completing 24±1 session (average heart rate= 0.89±0.029% HRmax). Fasting blood samples were taken and body mass index was measured pre- and post-intervention.Results: In CON, there was not significant change in all measured variables before and after the intervention period. Irisin increased (P<0.01) by 0.64±0.27 mg/ml in HIIT group. Insulin decreased (P<0.01) by 0.96±0.36 mg/dl while the blood lipid profile P= 0.78 cholesterol, P=0.14 TG, P=0.10 HDL, P=0.52 LDL, systolic blood pressure (P= 0.51), dyastolic blood pressure (P= 0.75), and BMI (P= 0.87) were unaltered.Conclusion: The result of present study showed that high intensity interval swimming trainings is an effectual and time-efficient training way for increasing irisin, and it can lead to compensatory irisin increases in postmenopausal overweight women.